Monthly changes of collembolan population under the gradients of moisture, organic carbon and nitrogen contents in a sub-tropical forest soil, Manipur. - Mema Devi, W; Singh, Th Binoy; Joymati Devi, L (Journal of Experimental Sciences, 2012)
Population study of collembola for one calendar year was made in relation with moisture, organic carbon and nitrogen contents of a sub-tropical forest floor upto 0-10 cm. soil layer. Soil moisture content played important role and developed a significant correlation (p>0.01) with the monthly population density of collembola. With increase carbon and nitrogen contents also observe increase population density indicating collembolaâ€™s active participation in the release of these two nutrients from litter through decomposition and its incorporation in soil fertility.Â 